Accelerated Aging of Dual-Layer Cables System Used in Nuclear Power Plants: A Degradation Pathway Study - Samuel Escobar Veras; Stephanie S. Watson; Gerardo Morell; Brad R. Weiner (IEEE Access)
This study explores the degradation behavior of cable insulation under simulated aging conditions, specifically focusing on monitoring thermal properties. The insulations, used in nuclear power plants (NPPs), are a two-layer system composed of chlorinated polyethylene elastomer (CPE) for the bonded jacket (L2) and ethylene propylene rubber (EPR) for the insulator (L1). Degradation was monitored via Fourier-transform infrared spectroscopy (FTIR) spectroscopy and Differential Scanning Calorimetry (DSC). Our results revealed a gradient degradation between the external and internal sides of the bonded jacket layer, L2, while L1 demonstrated a homogeneous degradation pattern. Notably, the external surface of L2 exhibited significant oxidation, while the internal surface showed an increase in methylene groups, due to low molecular mass degradation products from the external surface. These findings provide crucial insights into cable degradation processes, highlighting that, multiple phenomena, such as oxidation, chain scission, and cross-linking occur simultaneously. The results have implications for the safety and maintenance of NPP (e.g., cable aging management programs during long-term operations).